A Critical Analysis of Fuzzy Logic Controller for Slip Control in Antilock Braking System (ABS) - N. Zohedi, Fauzal; A.Rahmat, M.; A.Kasdirin, Hyreil (International Journal of Engineering and Technology, 2018)
This project aims at proposing an innovative way to implement the concept of fuzzy logic to an ABS model. The implementation of this project was conducted using simulation of ABS which is a combination from vehicle speed, wheel speed and slip through MATLAB Simulink software. By implementing fuzzy logic to the ABS system, the fuzzy logic can facilitate in improving the ABS abilities. The ABS model is developed and fuzzy logic controller is implemented to the model. The performance of the Fuzzy ABS is analyzed. The result shows that the fuzzy logic controller can facilitates the performance of the ABS by reducing the stopping time and maintaining the slip value near to 0.2.Â Â